Home, land, security: deradicalization and the journey back from extremism - Power, Carla (One World, 2021)
Introduction -- Part I : children who leave, mothers who wait -- You're the mother of a terrorist -- The godmother and her God-daughters -- Part II : change makers -- The 'terrorist drop-off center'-on meeting the be-header -- Loss of faith -- Only God knows you're the mother of a terrorist -- The human heart -- Part III : a wider view -- American blow back -- Taking responsibility -- How To de-radicalize your town